2005
DOI: 10.1038/sj.ejcn.1602164
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Trp64Arg polymorphism of the β3-adrenergic receptor gene in healthy and obese Hungarian children and its association with cardiovascular risk factors

Abstract: Objective: To estimate the frequency of Arg64 allele of the b 3 -adrenergic receptor (3-BAR) gene in healthy (H) and obese (O) Hungarian children, and to look for possible associations between this polymorphism and some clinical and metabolic characteristics of obese children. Patients/methods: In all, 147 healthy (male: 68) and 295 obese (male: 168) children were examined. The average age of the children in the two groups was 12.471.7 vs 12.673.2, respectively. Exon 1 of 3-BAR was amplified by polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Moreover, in postmenopausal Polish women, the frequency of MS was reported to be higher (22%) in women with the Trp64Arg polymorphism than without (14%) . In children, only a few previous studies have reported significant associations between Trp64Arg polymorphism and high blood pressure, high insulin and HOMA‐IR or low HDL‐C . No previous studies have assessed the relationship between Trp64Arg polymorphism and all of the MS components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in postmenopausal Polish women, the frequency of MS was reported to be higher (22%) in women with the Trp64Arg polymorphism than without (14%) . In children, only a few previous studies have reported significant associations between Trp64Arg polymorphism and high blood pressure, high insulin and HOMA‐IR or low HDL‐C . No previous studies have assessed the relationship between Trp64Arg polymorphism and all of the MS components.…”
Section: Discussionmentioning
confidence: 99%
“…Because ADRB3 is mainly expressed in fat cells of VF tissue , dysfunction in this receptor may result in a predisposition to impaired lipolysis, resulting in VF obesity . Trp64Arg polymorphism in the ADRB3 gene has been reported to be significantly associated with whole body obesity, VF accumulation and other MS components or their cluster, both in adults and in children of various ethnic groups. In particular, Japanese people have higher frequencies of Trp64Arg polymorphism and VF accumulation, but less gynoid fat, than other ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the beta-3 adrenergic receptor is predominantly expressed in visceral adipose tissue (Krief et al, 1993). Notably, the Arg allele of this SNP has been linked with increased BMI, adiposity and obesity in children (Arashiro et al, 2003;Endo et al, 2000;Erhardt et al, 2005;Ochoa et al, 2004;Park et al, 2005) supporting the evidence in adults Pierola et al, 2007), and the increased risk for obesity at this ADRB3 loci may be driven partly by an interaction effect of the PPARG SNP Pro12Ala Hsueh et al, 2001;Ochoa et al, 2004). Other studies in young children between the ages 4-10 years and in adolescents report no signifi cant effects of Trp64Arg variants on BMI, weight or height when this variant is examined in isolation (Cecil et al, 2007;Haworth et al, 2008a;Hinney et al, 1997;Kurokawa et al, 2003).…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%
“…The β 3 ‐adrenergic receptor is mainly present in visceral fat and is responsible for thermogenesis in brown adipose tissue. Obese children had significantly higher blood pressure and levels of insulin if they carried the Arg64 polymorphism when compared to obese children without the Arg64 polymorphism . Although another study did not find a significant difference between carriers of variations in the β 3 ‐adrenergic receptor gene, systolic and diastolic blood pressure were highest in Trp64Arg homozygote children .…”
Section: Resultsmentioning
confidence: 92%